A Worse 10-Year Prognosis in T2DM Combined with Hypertension after Multi Factorial Intervention in Beijing Community. Issue 2 (2021) - Hu, Dongming; Gang, W; Deyuan, L; Cheng, S; Yucui, R; Xiao, J; Yanling, Z; Tao, B; Guijuan, G; M, M; Yanfang, L; Wang, Z; et al.
No abstract available